Two new species of Milnesium (Tardigrada: Milnesiidae) - Pilato, Giovanni; Sabella, Giorgio; Lisi, Oscar (Zootaxa, 2016)
Two new species of Milnesium are described: Milnesium vorax sp. nov from Sicily and Milnesium tumanovi sp. nov. from Crimea. Milnesium vorax sp. nov. is uncoloured, with eye spots, smooth cuticle, wide buccal tube, stylet supports inserted on the buccal tube at almost 62 % of its length; claws with configuration [2-3]-[3-2]; accessory points present on the main branches. Milnesium tumanovi sp. nov. is also uncoloured, has eye spots, smooth cuticle, and wide buccal tube, but it has the stylet supports inserted on the buccal tube at about 52 % of its length, and claws with configuration [3-3]-[3-3]; the accessory points are present on the main branches.